On-substrate joule effect heating by printed micro-heater for the preparation of ZnO semiconductor thin film - Tran, Van-Thai (2020)
Fabrication of printed electronic devices along with other parts such as supporting structures is a major problem in modern additive fabrication. Solution-based inkjet printing of metal oxide semiconductor usually requires a heat treatment step to facilitate the formation of target material. The employment of external furnace introduces additional complexity in the fabrication scheme, which is supposed to be simplified by the additive manufacturing process. This work presents the fabrication and utilization of micro-heater on the same thermal resistive substrate with the printed precursor pattern to facilitate the formation of zinc oxide (ZnO) semiconductor. The ultraviolet (UV) photodetector fabricated by the proposed scheme was successfully demonstrated. The performance characterization of the printed devices shows that increasing input heating power can effectively improve the electrical properties owing to a better formation of ZnO. The proposed approach using the on-substrate heating element could be useful for the additive manufacturing of functional material by eliminating the necessity of external heating equipment, and it allows in-situ annealing for the printed semiconductor. Hence, the integration of the printed electronic device with printing processes of other materials could be made possible.